Lifelong learning - Holmes, Andrew (ExpressExec life & work, 2002)
Covers the key techniques of lifelong learning, from keeping a learning log and a self-development plan to finding a personal coach/mentor and getting yourself published. This title features examples and lessons from successful companies that generate a continuous learning culture including Barclays and The Leverage Organisation.